Improving the Utility of High Resolution Manometry for the Diagnosis of Defecatory Disorders in Women with Chronic Constipation - Sharma, Mayank (Neurogastroenterol Motil, 2020)
BACKGROUND. We compared the utility of existing and modified versions of high resolution manometry for diagnosing defecatory disorders (DD). METHODS. In 64 healthy and 136 constipated women, we compared left lateral (LL) and seated manometry, analyzed with existing (Manoview™) and new methods, for discriminating between constipated patients with normal and prolonged rectal balloon expulsion time (BET). In both positions, the rectoanal gradient (RAG), and for the new analysis, the pressure topography pattern during evacuation, were used to discriminate between constipated patients without and with DD. KEY RESULTS. The BET was prolonged, suggestive of a DD, in 52 patients (38%). During evacuation, rectoanal pressures and the RAG were greater in the seated than the LL position (P≤.001). In the seated position, the BET was associated with the pattern (P=.0001), being prolonged in respectively 45%, 15%, 53%, and 0% of patients with minimal change, anal relaxation, paradoxical contraction, and transmission. Within each pattern, the RAG was greater (ie, less negative, P<.0001) in patients with a normal than a prolonged BET. Compared to the Manoview™ RAG in the LL position, the integrated analysis (ie, pattern and new RAG) in the LL position (P<.01) and the seated Manoview™ gradient (P=.02) were each more effective for discriminating between constipated patients without and with DD. CONCLUSIONS & INFERENCES. Anorectal HRM ideally should be performed in the more-physiological seated position, and analyzed by a two-tier approach which incorporates the overall pattern followed by the rectoanal gradient. These findings reinforce the utility of manometry for diagnosing DD.